The role of ultrasound in the diagnosis and management of carpal tunnel syndrome: a new paradigm - KANE, DAVID (My University, 2015)
Carpal tunnel syndrome (CTS) is the most common entrapment neuropathy, affecting 9% of women, and it is responsible for significant morbidity and occupational absence. Clinical assessment is used for initial diagnosis and nerve conduction (NC) studies are currently the principal test used to confirm the diagnosis. Sensitivity of NC studies is >85% and specificity is >95%. There is now good evidence that US can be used as an alternative to NC studies to diagnose CTS. US can assess the anatomy of the median nerve and also identify pathology of the surrounding structures that may compress the nerve. Median nerve enlargement (cross-sectional area ≥10 mm(2) at the level of the pisiform bone or tunnel inlet) is the most commonly used parameter to diagnose CTS on US, and sensitivity has been reported to be as high as 97.9% using this parameter. US may also be used to guide therapeutic corticosteroid injection into the carpal tunnel--thus avoiding median nerve injury--and to objectively monitor the response to treatment. There is now sufficient evidence to propose a new paradigm for the diagnosis of CTS that incorporates US. US is proposed as the initial diagnostic test in CTS based on similar sensitivity and specificity to NC studies but higher patient acceptability, lower cost and additional capability to assess carpal tunnel anatomy and guide injection.
PUBLISHED
Keywords: carpal tunnel syndrome